Vascular Diameters as Predictive Factors of Recanalization Surgery Outcomes in Internal Carotid Artery Occlusion - Yan, Chengrui; Wang, Jiaru; Guo, Ruohan; Jin, Weitao; Zhao, Yang; Wang, Rong (Frontiers in Neurology, 2021)
Background: Revascularization surgery sometimes can achieve recanalization in patients with internal carotid artery occlusion (ICAO). High-resolution vessel wall magnetic resonance imaging (HRVWI) is a feasible technique to give detailed characteristics of the vessel wall, which may help to identify patients that carry higher success rates and more suitable for revascularization surgery. Objective: To examine the association between HRVWI characteristics of ICAO and the success rate of revascularization surgery in ICAO patients. Methods: We conducted a retrospective analysis of 31 ICAO recanalization patients enrolled from October 2017 to May 2019. The clinical data of patients and lesions were collected and analyzed. Results: A total of 31 ICAO patients were enrolled in this study. No significant differences were found between recanalization success and recanalization failure groups with regard to occlusion length, distal end of the occluded segment, and the treatment applied. The ipsilateral-to-contralateral diameter ratios (I/C ratios) of C1 or C2 and the diameter of C7 were positively related to recanalization success. A two-factor predictive model was constructed, and the I/C ratio of C2 < 0.86 and the diameter of C7 < 1.75mm were separately assigned 1 point. The ICAO patients who scored 0, 1, or 2 points had a risk of 5.6% (1/18), 55.6% (5/9), or 100% (4/4) to fail in the recanalization. Conclusions: The I/C ratios of C1 or C2 and the diameter of C7 are predictive factors of a revascularization surgery success in ICAO patients. A risk stratification model involving C2 and C7 was constructed for future clinical applications.